In Search of the Invisible People: Revisiting the Concept of "Internally Displaced Persons" in Light of an Ethiopian Case Study. (7th February 2022) - Regasa, Dereje; Lietaert, Ine
Abstract: Internal displacement has become one of the most pressing humanitarian crises today, with the Global South being especially affected. Despite this, internally displaced persons (IDPs) remain underrepresented in humanitarian policy and academia. While attention for IDPs is increasing, the extent to whether the label actually embraces all circumstances of internal displacement can be questioned. We argue for a revision of contextualisation and conceptualisation of IDPs. Hence, drawing on a survey of literature and concrete examples from Ethiopia, the article revisits the concept of IDPs with the central aim of broadening its understanding. By tracing its emergence, evolution, and underlying assumptions, the findings show that the IDP label dominantly refers to displaced people in refugee-like situations. As a result, a large number of IDPs, such as those who are forcedly resettled and left unintegrated, are rendered invisible. Concretising processes of displacement within the Ethiopian case further illustrates the impacts of narrow conceptualisations and consequently, advances insights into possible drivers and types of IDPs. This illustrates the need for the scholarship to go beyond policy labels and adopt a contextualised understanding of IDPs while also contributing towards improving research and governance on the subject of IDPs.